A Case Study on Orphan’s Grit - Hidayah, Rifa (Proceedings Conference Psychology and Flourishing Humanity; Vol 1 No 1 (2024): Proceedings Conference on Psychology and Flourishing Humanity, 2025)
Orphans need support in living this life, and need grit in their lives, including in their education. This study aims to analyze the picture of an orphan’s grit, and the factors that influence grit. The research method is qualitative research in case study. Data were collected through interviews, observations and psychological tests. Research respondent one orphan living in an orphanage “X”. The results showed that orphans have good grit, and the factors that influence grit, namely individual factors and social support factors, such as from peers and the surrounding environment. The findings in this study are expected to be a contribution, especially for orphans, to be optimistic and do their best in achieving the future.